Vivencias de las mujeres violentadas que denuncian su caso. Sucúa periodo diciembre 2020 - mayo 2021 - Gavilánez Gavilánez, Melyna Isabel (2021)
The purpose of the case study was to learn about the life stories of the women who have reported their cases to the corresponding bodies, delving deeper into the risk factors of gender-based violence. The present research work corresponds to a qualitative type, with a phenomenological approach, with a descriptive design focused on data collection based on in-depth interviews in a focus group, with a type of non-probabilistic and convenience sampling established by the researchers. The categories found in the case study were "Mi idea abur viólense", "Viólense in mi Daisy rife", "Tellina mi pan", "Mi behaviour in the face of violence", "Feeling violence", "Marching towards change", "Receiving support", "My life advice". From the life stories it can be deduced that the women have received all kinds of aggression or physical, psychological and even sexual mistreatment throughout their affective relationships, making them feel denigrated, it is worth mentioning that the violence has been in private, even in front of third parties. It has also been shown that these women have experienced violence since childhood; and that the reason for enduring violence has been mainly because they depend on their partners emotionally and economically. On the other hand, they recognise that after the denunciation they have worked hard to raise their self-esteem, they have received support from their families and institutions to overcome the violence with courage. Another risk factor for gender-based violence was the lack of education on these issues, and the lack of awareness in society to prevent violence. Keywords: Women, violence, complaints, experiences.